2016
DOI: 10.1038/srep21112
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretching stimulates collagen synthesis via down-regulating SO2/AAT1 pathway

Abstract: The aim of the study was to investigate the role of endogenous sulfur dioxide (SO2)/ aspartate aminotransferase 1 (AAT1) pathway in stretch-induced excessive collagen expression and its mechanism. The mechanical stretch downregulated SO2/AAT1 pathway and increased collagen I and III protein expression. Importantly, AAT1 overexpression blocked the increase in collagen I and III expression, transforming growth factor-β1 (TGF- β1) expression and phosphorylation of Smad2/3 induced by stretch, but AAT1 knockdown mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…8,27,28 Our previous studies found that SO 2 could alleviate abnormal collagen accumulation in small pulmonary arteries of hypoxic pulmonary hypertensive rats and in a mechanical stretch- stimulated cell model. 29,30 In our previous research, 11 the pulmonary vascular structural remodeling induced by monocrotaline was confirmed by an increase in the relative medial thickness and area of pulmonary arteries. With inhibition of endogenous SO 2 production by HDX, pulmonary arterial remodeling became worse in the monocrotaline plus HDX group than in the monocrotaline group, indicating that inhibition of endogenous SO 2 could aggravate pulmonary vascular remodeling in monocrotaline-treated rats.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…8,27,28 Our previous studies found that SO 2 could alleviate abnormal collagen accumulation in small pulmonary arteries of hypoxic pulmonary hypertensive rats and in a mechanical stretch- stimulated cell model. 29,30 In our previous research, 11 the pulmonary vascular structural remodeling induced by monocrotaline was confirmed by an increase in the relative medial thickness and area of pulmonary arteries. With inhibition of endogenous SO 2 production by HDX, pulmonary arterial remodeling became worse in the monocrotaline plus HDX group than in the monocrotaline group, indicating that inhibition of endogenous SO 2 could aggravate pulmonary vascular remodeling in monocrotaline-treated rats.…”
Section: Discussionmentioning
confidence: 81%
“…SO 2 exerts important effects on the cardiovascular system, such as vasorelaxant and negative inotropic effects . Our previous studies found that SO 2 could alleviate abnormal collagen accumulation in small pulmonary arteries of hypoxic pulmonary hypertensive rats and in a mechanical stretch‐stimulated cell model . In our previous research, the pulmonary vascular structural remodeling induced by monocrotaline was confirmed by an increase in the relative medial thickness and area of pulmonary arteries.…”
Section: Discussionmentioning
confidence: 85%
“…Mechanical strain is a known inducer of ECM remodeling in a number of tissues and organs, such as skin, 15 lung tissue, 11,16 bone, 17 and vascular systems. 18 Alterations include cell reorientation, matrix composition, collagen, and elastin realignment.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of SO 2 derivatives (0.54 mmol/kg: 0.18 mmol/kg, for eight weeks) could significantly reduce the mean pulmonary artery pressure and improve the pulmonary vascular pathological changes of the rats, as demonstrated by the decreased percentage of muscularized pulmonary arteries. Furthermore, Liu et al [ 46 ] found that SO 2 alleviated the protein expression of collagen I and collagen III.…”
Section: So 2 and Vascular Remodeling In Hypertmentioning
confidence: 99%